GLOBAL ECONOMIC SPACE IN THE AGE OF DIGITAL ECOLOGIZATION: CHALLENGES AND PROSPECTS (INNOVATIVE ECONOMY, 2025)
Korniienko D.B. GLOBAL ECONOMIC SPACE IN THE AGE OF DIGITAL ECOLOGIZATION: CHALLENGES AND PROSPECTSPurpose. The aim of the article is to analyze the current state and prospects of digital greening in the global economic space, highlighting the main policy directions and technological solutions.Methodology of research. The methodological basis of the study is a combination of qualitative and quantitative approaches, which ensures depth of analysis and the possibility of verifying the results. In particular, methods of systematic analysis, comparative analysis, content analysis of regulatory and legal acts of individual countries, as well as analysis of reports of international organizations (UNEP, OECD, World Bank) were used. Data from open sources were analyzed, including statistical databases (Eurostat, IEA, Statista), analytical platforms (McKinsey Insights, Deloitte Reports), and scientific publications in Scopus/Web of Science. Graphs and charts created in Tableau and Microsoft Excel were used to illustrate the empirical data. An interdisciplinary approach was applied, including analysis of regulatory acts, review of analytical reports, and comparative analysis of cases of digital eco-technology implementation in different countries.Findings. It has been found that in the context of modern challenges of climate change, resource depletion, and digitization of economies, digital greening emerges as a key paradigm of sustainable development of the global economic space. The current challenges, prospects, and directions of digital greening development in the international context have been substantiated and researched. Regional differentiation in digital greening has been identified and substantiated, i.e., it has been determined that EU countries demonstrate a high level of integration of digital eco-technologies, while China and the US apply them in specific sectors (environmental monitoring, ESG analytics), while countries of the Global South are characterized by fragmented practices that depend on international support. The main barriers to digital transformation in an environmental context have been identified, and the prospects for integrating environmental digital innovations into national and corporate development strategies have been outlined. Originality. The interpretation of “digital greening” as a new paradigm of the global economic space, integrating digital technologies (IoT, AI, Big Data, digital twins) with environmental management mechanisms to achieve sustainable development goals, has been further developed.Practical value. The practical value of the work lies in summarizing the experience of leading countries in the field of digital greening, which can be used to shape sustainable development policies in Ukraine and beyond. The provisions developed can be used to shape state policy in the field of digital greening, particularly in the context of fulfilling commitments under the Sustainable Development Goals and the European Green Deal.Key words: digital greening, sustainable development, global economic space, digital innovation, green transition, eco-technologies, digital transformation.
Keywords: digital greening; sustainable development; global economic space; digital innovation; green transition; eco-technologies; digital transformation